answersLogoWhite

0

x^(2) - 4y^(2)

Before calculating , we note

#1 ' There is a negative sign between the two squares. So it will factor

#2 ' '4' is the square of '2' . So we can redraw the terms as ( 2y)^2

Hence

x^(2) - (2y)^2)

This now satisfies the two conditions above. . So it will factor to

( x - 2y)(x + 2y)

Note the different signs in each bracket .

You hve asked for it to be solved!!! To solve you need to equate the terms to a value. In this case use '0'

Hence

(x - 2y)(x + 2y) = 0

Taking each bracket in turn

x - 2y = 0

x = 2y or 2 = x/y or y = x/2

Then

x + 2y = 0

x = -2y or -2/x/y or y = x/-2

Are the possible forms of solution.

NB If you have two squared terms and a positive (+) between them, then it does NOT factor.

NNB Think of the Pythagorean Equation

a^2 + b^2 = h^2 This DOES NOT factor.

However

a^2 = h^2 - b^2 (Algebraic rearrangement) , DOES factor to

a^2 = (h - b)(h + b)

User Avatar

lenpollock

Lvl 16
12mo ago

Still curious? Ask our experts.

Chat with our AI personalities

SteveSteve
Knowledge is a journey, you know? We'll get there.
Chat with Steve
MaxineMaxine
I respect you enough to keep it real.
Chat with Maxine
ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
More answers

It is not clear what you want to solve for.

User Avatar

Wiki User

13y ago
User Avatar

Add your answer:

Earn +20 pts
Q: How do you solve x squared minus 4 y squared?
Write your answer...
Submit
Still have questions?
magnify glass
imp